AI for good : Applications in sustainability, humanitarian action, and health - Ferres, Juan M.Lavista (UK John Wiley & Sons, 2024)
The book is an insightful and fascinating discussion of how one of the world$1 (Bs most recognizable software companies is tacking intractable social problems with the power of artificial intelligence (AI). In the book, you$1 (Bll learn about how climate change, illness and disease, and challenges to fundamental human rights are all being fought using replicable methods and reusable AI code.s